2020
DOI: 10.1177/1934578x20912088
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activities of Kukoamine A From the Root Bark of Lycium chinense Miller

Abstract: Kukoamine A (Kuk A) is a naturally occurring bioactive spermine alkaloid found in the root bark of Lycium chinense, and it exerts various therapeutic effects including antioxidant, neuroprotective, anti-inflammatory, and antidiabetic effects. This study evaluated the anti-inflammatory properties of Kuk A against lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophage cells and carrageenan-induced paw edema in rats. Pretreatment of cells with Kuk A significantly inhibited the production of reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…(2014) investigated the anti-inflammatory properties of Gingerone and their inherent cosmetic use as an anti-ageing agent. Kukoamine A, Euparin and Aloresin are other components with anti-inflammatory properties as reported by Wang et al. (2020) , Xiao et al.…”
Section: Resultsmentioning
confidence: 75%
“…(2014) investigated the anti-inflammatory properties of Gingerone and their inherent cosmetic use as an anti-ageing agent. Kukoamine A, Euparin and Aloresin are other components with anti-inflammatory properties as reported by Wang et al. (2020) , Xiao et al.…”
Section: Resultsmentioning
confidence: 75%
“…Of them, five major compounds shown in Figure 8 A, eluted at RT of 5.14 min (P1), 8.37 (P2), 9.61 (P3), 9.98 (P4), and 11.06 (P5), were identified as kukoamine A or kukoamine B (P1), 4-[4-(tert-butoxycarbonyl)piperazin-1-yl]benzoic acid (P2), n -caffeoyltyramine (P3), lyciumin A (P4), and coumarin 314 (P5), respectively ( Figure 8 B and Table 1 ). These compounds, including betaine, have been reported for their anti-inflammatory activities [ 18 , 25 , 26 ], and thus, the observed anti-inflammatory and protective effects of GR30 against PM10-mediated inflammation and basophil cell death could be attributed to these compounds present in GR30.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the roots of these traditional medicinal plants, only a small portion of their bark (Lycii Radicis Cortex, LRC) has been traditionally utilized in Korea (under the name of Jigolpi) and China (known as Digupi) for the cure of various symptoms. However, other than the use of their bark (LRC), their whole roots have attracted relatively less attention and have just been discarded as by-products from the Goji farm yards, although they still contain various bioactive substances [ 15 , 16 , 17 , 18 ]. Several recent studies reported that the roots of Lycium species also exhibit various beneficial health effects [ 15 ], such as antioxidant [ 19 ], antitumour [ 20 ], anti-osteoclastic [ 21 ], antimicrobial [ 22 ], and immunomodulatory activities [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the compounds that were confirmed in the negative mode consisted of 32 compounds, including sanjoinine A, Quinic acid, and Kukoamine A, these three compounds also have biological activity that can contribute medicinally, namely the compound sanjoinine A, which has potential as an antioxidant (Foyet et al, 2019). In addition, Quinic acid compounds also have the potential for hepatoprotective, anti-inflammatory, antioxidant activity and the treatment of dengue virus infection and prostate cancer (Zanello et al, 2015); while the compound kucoamine A has been shown to have antioxidant, anti-inflammatory, and anticancer activities (Li et al, 2017;Wang et al, 2020;Wang et al, 2016).…”
Section: Lc-ms/ms Qtof Analysis Of Ziziphus Mauritiana Fruit Juicementioning
confidence: 99%